Przemoc a kobiety w ujęciu feministycznym. Wybrane problemy - Helios, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of the present work is an attempt to analyze the concept of violence in the context of women with regard to feminism. In the text I try to point out that women can act in a dual role as: victims and perpetrators of violence/crime. Statistics show that women are less likely to resort to violence than men. However, this does not mean that women do not use violence. Violence is not related to gender. This thesis has been criticized by feminism, which rather focuses on women as victims of violence. The first part of the article discusses two stereotypes of violence based on gender. The second part of the study is devoted to the issue of violence on the basis of regulations of criminal law. They indicated on the one hand, the most common types of crimes committed by women, and on the other, crimes of which women are victims most representative is the crime of rape.
Keywords: przemoc; feminizm; kobiety; płeć; prawa kobiet; przestęsptwo gwałtu